Beautiful redemption - Garcia, Kami (Garcia, Kami. Beautiful creatures novel, 2012)
When Ethan wakes after the chilling events of the Eighteenth Moon, his one goal is to return to Lena and his loved ones, while back in Gatlin, Lena vows to do whatever it takes to bring Ethan home--even trusting old enemies and risking the lives of those Ethan left to protect.